Engineering reciprocal chromosomal translocations to control the fate of populations - Akbari, Omar (Henry Stewart Talks, 2018)
Why mosquito-borne diseases are so deadly, Commonly used practices for mosquito control, Engineering mosquitoes to resist infection, Gene drive systems, Genetic outcrossing, Engineering translocations & use of CRISPR, Inserting pathogen resistance genes, Replacing the wild population